Implementation and analysis of a telephone support service during COVID-19. (25th May 2020) - Matthewson, J; Tiplady, A; Gerakios, F; Foley, A; Murphy, E
Abstract: Background: During the COVID-19 pandemic, it has been essential for occupational health services (OHS) providers to react rapidly to increased demand and to utilize resources in novel ways. The impact of the COVID-19 pandemic on the psychological well-being of staff is already identified as an area of high risk; therefore, providing timely access to psychological support may be vital, although limited evidence is available on how these risks are best managed. Aims: To describe implementation and analysis of a psychology-led COVID-19 telephone support line in a National Health Service OHS. Methods: Data from calls made to the support line were collected over the first 4 weeks of service implementation. Numerical data including frequency of calls and average waiting time were first considered. A content analysis was then conducted on call notes to identify prevalence of themes. Results: Six hundred and fifty-five calls were received, and 362 notes included sufficient information for use within the content analysis. Frequency of calls peaked within the first week followed by a reduction in the number of calls received per day over time. Most calls included discussion around clarification of guidance (68%) with a smaller subset of calls offering support around anxiety (29%). Prevalence of themes did not appear to change over time. Conclusions: Clear and timely information is vital to support the well-being of healthcare staff. A psychologically informed telephone support line was a good use of occupational health service resources in the interim while more tailored advice and services could be established.